2023
DOI: 10.3390/vaccines11020283
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and SARS-CoV-2 Infection following the Fourth BNT162b2 Booster Dose among Health Care Workers

Abstract: Introduction: The fourth SARS-CoV-2 vaccine dose was found to protect against infection and more importantly against severe disease and death. It was also shown that the risk of symptomatic or severe disease was related to the antibody levels after vaccination or infection, with lower protection against the BA.4 BA.5 Omicron variants. The aim of our study was to assess the impact of the fourth dose on infection and perception of illness seriousness among healthcare workers (HCWs) at a tertiary health care camp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In our analysis of antibody dynamics in previously infected and uninfected participants using linear regression, we observed that the previously infected group maintained more sustained antibody levels over time compared with the uninfected group 13 , 14 . In uninfected participants, predicted antibody levels fell below 1000 arbitrary units per milliliter (AU/mL) in approximately 220 days; in those previously infected, the predicted antibody levels remained above 1000 AU/mL even after 400 days (Fig.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…In our analysis of antibody dynamics in previously infected and uninfected participants using linear regression, we observed that the previously infected group maintained more sustained antibody levels over time compared with the uninfected group 13 , 14 . In uninfected participants, predicted antibody levels fell below 1000 arbitrary units per milliliter (AU/mL) in approximately 220 days; in those previously infected, the predicted antibody levels remained above 1000 AU/mL even after 400 days (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…Our population-based follow-up study corroborated that individuals with prior infection maintained their antibody levels over time following additional vaccinations, compared with those not previously infected with COVID-19. Previous reports suggest that antibody levels below 1000 binding antibody units per milliliter (BAU/mL) are associated with a significantly increased risk of Omicron-strain infection 13 , 14 . The unadjusted linear regression performed to visually illustrate the temporal changes in antibody titers between groups in our study also suggested that individuals with prior infection retained antibody levels exceeding 1000 AU/mL, often considered indicative of reduced infection risk, for over 400 days.…”
Section: Discussionmentioning
confidence: 99%
“…The attenuated response to the VOC epitopes was reported in infected patients with the prior Wuhan-Hu-1-like antigen vaccination, compared with unvaccinated infected patients [ 32 ]. Recently, during the Omicron VOC outspreading, multiple studies demonstrated that the fourth (second booster) dose raised a milder immune response and rapidly waned, compared to the previous vaccination [ 36 , 37 ]. This phenomenon might be explained by the OAS theory.…”
Section: Discussionmentioning
confidence: 99%